Avaliação do atual potencial de reúso de água no Estado do Ceará e propostas para um sistema de gestão - Caixeta, Cláudia Elizângela Tolentino (2010)
The main objective of this work was evaluate the potential for water reuse in the state of Ceara as a contribution to the effective management of water resources and the conservation of the state. It consisted of the following stages: (1) literature, (2) A bibliographical survey; (2) description of the Ceara State (area under study); (3) definition of alternatives and criteria for reuse, (4) survey of treatment plants with respective flow rates and characteristics of treatment system for selection of those whose effluent can be used, (5) proposition (s) type (s) to reuse the selected treatment plants, (6) economic feasibility study for the financial reuse industrial (7) conditions of proposition and guidelines for the strengthening of reuse in the State, (8) present and discuss the results and (9) assessing the work undertaken. As results of the study we can mention: (1) The industrial reuse was feasible to be deployed in DI Maracanaú, and the effluent standard type 2 (effluent from the stabilization pond, mixing tank for pH correction, flocculant, decantor, carbonation tank and final effluent) showed the best economic and financial viability. (2) Research conducted with companies in the DI Maracanaú showed great responsiveness on the part of potential users, since it is guaranteed quality, quantity and price competitive with current power supply. (3) Of the 12 systems evaluated the Tupamirim WTPT presented the best conditions for the practice of non-potable urban reuse - irrigation of green areas in Fortaleza (4) The system of stabilization ponds in operation in the RMF and the State can provide a flow of about 1872.0 L / s, and these volumes will benefit approximately 3279.66 hectares, whereas the demand for irrigation equal to18,000 m3/ha.ano, or supply, on average, a growing area of 1,497,600 m2 fish (149.7 ha). The main conclusions of this work are: (1) The implementation of water reuse in Ceará is an important alternative to be considered in the State Plan for Water Resources, as it may: contribute effectively in the conservation of water resources, increase the supply of water for agricultural, fish and industry in the state, through the provision of reclaimed water for uses that can dispense the drinking, and provide a greater volume of water of good quality to end uses, as recommended by Agenda 21.(2) Among the types of reuse study for the state, all proved viable. As the industrial reuse which will require a larger investment. Since the re-use agricultural and fish are the easiest to implement, requiring only a determination of the State Government so that it signed a partnership betweean Cagece and SDA thus enable the implementation of projects.(3) The reuse of wastewater in the state of Ceara is a viable alternative, but necessary regulations to mitigate the pest risk that may arise from the practice without the adoption of multiple barriers to ensure protection of population health. Is no denying the need to establish guidelines that allow the practice of reuse to become secure, ubiquitous, thus helping to minimize the problem of water scarcity in the state.